Good Laboratory Practice (GLP) in The European Union - Viviane Annisa; Jafar La Kilo (Jurusan Farmasi Universitas Negeri Gorontalo, 2022)
GLP (Good Laboratory Practice) regulations regulate how to work in laboratories, personnel training, standard operating procedures, software for data recording, documentation, etc. The main goal of GLP is to improve the quality of data testing so that each country can produce continuous and continuous testing of data, avoid repeated testing, and save time. The members of the OECD (Organization for Economic Co-operation and Development) are 29 countries around the world, including Asia-Pacific, America, and Europe. Adherence to the GLP can remove trade barriers between member countries. The GLP principles applied in the European Union are similar to those of the OECD, namely to improve the quality of testing valid data. This study aims to review about Good Laboratory Practice in European Union. The European Union adopted the GLP regulations in 1987. The amendments related to the GLP were carried out following the OECD in 1999. The EU regulatory regulations on GLP 'Directive 2004/9/EC' was later added 'Directive 88/320/EEC' explaining what was given to member states of the Union Europe to establish GLP inspections in each region and Mutual Acceptance of Data (MAD) requirements. Â Non-clinical testing of medicinal products in accordance with the provisions of the GLP refers to the OECD and European Union legislation consisting of 'Directive 2004/10/EC' and 'Directive 2004/9/EC'.